Comprehensive assessment of technical health with respect to the indicators of the level of hope - Abilmazhenov, Талгат; Kozhakhmet, Мейрам; Burkitbayev, Аян (Рroblems of engineering and professional education, 2023)
The modern methods of technical inspection of building are briefly illuminated from position of providing of the required quality to the level of reliability. Positions of operating normative documents are analysed in area of inspection and estimation of the technical state of building, the prospects of development of methods of technical inspection are offered in modern terms